The Effect of Brand Associations and Brand Awareness on the Decision to Buy a Sim Card - Yayuk Yuliana Yayuk; Mardi Giwa Putra (Yayasan Ilomata, 2020)
In the rapid development of technology, the business world is required to compete in this globalization era. The company is expected to keep abreast of technological developments accompanied by producing goods that are in accordance with the times and are full of innovative. Considering now, cellphone is a necessity item that cannot be separated from daily life, of course, causing increasingly fierce competition between cellulair operators to attract the attention of consumers to want to use and remain loyal to their products. This is the basis for thinking of this research with its long-term goal of creating a close and strong relationship with consumers through brand equity . In the context of creating loyal customers, the task of marketers is always not focused on the effort to practice marketing mix as the main strategy. The short-term goal is to analyze the influence of brand awareness and, brand associations. In relation to Sim cards more and more choices of goods and services make possibilities moving brands are higher, customers are less loyal so they need to get attention. The results obtained that there are three variables that have a significant effect partially, namely brand associations with a significance value of probabilities as α of 0,000 <0.05 while the calculated value> t table is 8.871> 0.1996. The results of the t test calculation of the Brand Awareness variable obtained the significance value of the probability α of 0.223> 0.05 while the value of t count <t table is -2222 <0.1996.